The dark hours ebook - Connelly, Michael (Renée Ballard, 2021)
A  Wall Street Journal and  South Florida Sun-Sentinel  Best Book of the Year “A masterpiece”—LAPD detective Renée Ballard must join forces with Harry Bosch to find justice in a city scarred by fear and social unrest after a methodical killer strikes on New Year’s Eve ( Publishers Weekly ). There’s chaos in Hollywood at the end of the New Year’s Eve countdown. Working her graveyard shift, LAPD detective Renée Ballard waits out the traditional rain of lead as hundreds of revelers shoot their guns into the air. Only minutes after midnight, Ballard is called to a scene where a hardworking auto shop owner has been fatally hit by a bullet in the middle of a crowded street party.   Ballard quickly concludes that the deadly bullet could not have fallen from the sky and that it is linked to another unsolved murder—a case at one time worked by Detective Harry Bosch. At the same time, Ballard hunts a fiendish pair of serial rapists, the Midnight Men, who have been terrorizing women and leaving no trace.   Determined to solve both cases, Ballard feels like she is constantly running uphill in a police department indelibly changed by the pandemic and recent social unrest. It is a department so hampered by inertia and low morale that Ballard must go outside to the one detective she can count on: Harry Bosch. But as the two inexorable detectives work together to find out where old and new cases intersect, they must constantly look over their shoulders. The brutal predators they are tracking are ready to kill to keep their secrets hidden.   Unfolding with unstoppable drive and nail-biting intrigue, The Dark Hours shows that “relentless on their own, Ballard’s and Bosch’s combined skills…could be combustible” ( Los Angeles Times ).